The last party - Mackintosh, Clare (Sourcebooks Landmark, 2022)
"Tucked into the mountains of North Wales, the village of Cwm Coed is bordered by a shimmering lake on one side and an army of pine trees on the other. But the tranquility is shattered when homegrown celebrity Rhys Lloyd returns to develop a luxury resort on the shore opposite the village. Old resentments begin to rise to the surface, and new tensions emerge between the locals and the outsiders. Still, when the resort throws open its doors for a New Year's Eve party, with champagne flowing through the night, none of the villagers can resist the invitation. The next morning, a body is found floating in the lake-and it's Rhys. Ffion Morgan is summoned to investigate, but with her deep ties to the village she dreads what she might find out about her neighbors, friends and family. And what about her own link to the victim?"--